NUSAP1 Promotes Gastric Cancer Tumorigenesis and Progression by Stabilizing the YAP1 Protein - Guo, Hui; Zou, Jianping; Zhou, Ling; Zhong, Min; He, Yan; Huang, Shanshan; Chen, Jun; Li, Junhe; Xiong, Jianping; Fang, Ziling; Xiang, Xiaojun (Frontiers in Oncology, 2021)
The Yes-associated protein (YAP1) is a main effector of the canonical Hippo pathway, which contributes greatly to tumor initiation, progression, and metastasis in multiple cancers, including gastric cancer (GC). Due to limited knowledge of YAP1 upregulation in cancer, it is a great challenge of therapeutic targets toward the Hippo–YAP1 pathway. Here, we identify nucleolar spindle-associated protein 1 (NUSAP1) as a novel binding partner of YAP1. The upregulation of NUSAP1 is associated with unfavorable clinical outcomes in GC patients, and NUSAP1 depletion impairs its oncogenic properties in vitro and in a xenograft model. Mechanistically, we discovered that NUSAP1 functions as a positive regulator of YAP1 protein stability, thereby inducing the transcription of Hippo pathway downstream target genes, such as CTGF and CYR61. More interestingly, we find that the cancer-promoting effects of NUSAP1 on GC cell growth, migration, and invasion are mainly mediated by YAP1. Furthermore, aberrant expression of NUSAP1 and YAP1 is highly correlated in GC cell lines and tissues. We herein clarify the role of the oncogenic NUSAP1–YAP1 axis in GC tumorigenesis and progression and, therefore, provide novel therapeutic targets for GC treatment.